Oxidative stress and alterations of antioxidant status in goats naturally infected with Mycoplasma agalactiae - Kizil, O.; Ozdemir, H.; Karahan, M.; Kizil, M. (Ecole Nationale Veterinaire Toulouse, 2007)
The aim of this study was to determine some oxidative stress parameters and antioxidant vitamin concentrations in goats naturally infected with Mycoplasma agalactiae. Forty seven goats showing clinical signs of contagious agalactia and 20 healthy goats (control group) were used in the study. Blood samples were taken from the jugular vein in order to measure the concentrations of vitamin A, E, C, P-carotene, glutathione (GSH) and malondialdehyde (MDA) and activities of catalase (CAT) and glutathione peroxidases (GSHPx), whereas milk and mastitic secretions were taken from the sick animals for M. agalactiae identification by culture and PCR. Significant increase of MDA concentrations, significant reductions of GSH, P-carotene, vitamin C and E concentrations and of GSHPx activity compared to the controls were evidenced in M. agalactiae infected goats. The results clearly demonstrate the occurrence of an oxidative stress leading to deficiency of enzymatic and non-enzymatic antioxidant systems during this infection.
Keywords: Mycoplasma agalactiae; goat; antioxidant vitamins; malondialdehyde; gluthathione peroxidases; catalase